Vaping-associated Lung Injury - Aftab, Ghulam (Cureus, 2019)
Many cases related to vaping-associated lung injury have recently been reported to the Center for Disease Control (CDC). It is, therefore, important for clinicians to be aware of this disease. Here, we present the case of a 46-year-old female patient, who had recently started vaping. She presented to the hospital with dyspnea; since her condition deteriorated quickly, she was mechanically ventilated for acute respiratory failure. When a computed tomography angiography (CTA) chest was performed, patchy alveolar opacities were seen throughout both lungs. The patient’s workup for infectious and cardiac etiology was negative. She was diagnosed with vaping-associated lung injury. Later, she recovered and was discharged to a rehabilitation center.